Correlates of Endothelial Function in Older Adults With Untreated Obstructive Sleep Apnea and Cardiovascular Disease. Issue 1 (January 2019) - Imes, Christopher C.; Baniak, Lynn M.; Choi, JiYeon; Luyster, Faith S.; Morris, Jonna L.; Ren, Dianxu; Chasens, Eileen R.
Abstract : Background: Obstructive sleep apnea (OSA) is a highly prevalent and consequential sleep disorder in older adults. Untreated moderate to severe OSA substantially increases the risk for hypertension and cardiovascular disease (CVD), which can be attributed to the accelerated progression of atherosclerosis and endothelial dysfunction. Objective: The aim of this study was to identify factors that can function as correlates of endothelial function in older adults with untreated, moderate to severe OSA and CVD or CVD risk factors. Methods: A subsample (N = 126) of adults aged 65 years and older from the HeartBEAT study were included in the analyses. Univariate analyses and multiple linear regression models were conducted to establish which demographic and CVD risk factors were the best correlates of endothelial function. Results: In the univariate analyses, sex, employment status, body mass index, waist circumference, hip-to-waist ratio, neck circumference, diastolic blood pressure, total cholesterol, high-density lipoprotein cholesterol, total cholesterol to high-density lipoprotein cholesterol ratio, plasminogen activator inhibitor-1, calcium channel blocker use, and β-blocker use were associated with endothelial function at a level of P < .10. In the most parsimonious model, male sex ( b = −0.305, P < .001), calcium channel blocker use ( b = −0.148, P < .019), and body mass index ( b = −.014, P < .037) were negatively associated with endothelial function after adjusting for the other covariates. Conclusions: The authors identified correlates of endothelial function in older adults with untreated OSA and CVD or CVD risk factors, which are different than the correlates in middle-aged adults with the same conditions.